Application of Harmony SE in civil aircraft design - LIU, Wanyi; FENG, Yunwen; HOU, Jieran; CHEN, Junyu; GUO, Yingnan (Xibei Gongye Daxue Xuebao, 2024)
With the refinement of civil aircraft technology and the enhancement of product complexity, civil aircraft design has changed from traditional text-based system engineering to model-based system engineering, the expression of the system has also transformed from text-centered to model-centered. To further improve the model quality and correctness of aircraft system modeling, this paper explores the applicability of model-driven and verification-oriented system engineering methods in the field of civil aircraft design, and establishes the system engineering practice framework of civil aircraft design, which can ensure the rapid design and efficient delivery of civil aircraft. Firstly, starting from the Harmony SE modeling method, the workflow and modeling ideas of system are introduced; then the noticeable problems in the practice of civil aircraft system engineering are analyzed, and the system engineering practice of civil aircraft design is established with the support of the applicability of the Harmony SE method; finally, the fuel tank pressurization component is taken as the research object of the practice system in component-level. The results show that the system engineering practice framework of civil aircraft design and method proposed in this paper can correctly and reasonably allocate design requirements and establish a complete system model, which is helpful to improve the efficiency and accuracy of civil aircraft design at this stage. 随着民用飞机技术精细化和产品复杂性的提高, 民用飞机设计已从传统的基于文档的系统工程转变为基于模型的系统工程, 系统表达也从以文档为中心转变为以模型为中心。为进一步提高民用飞机设计中系统建模的模型质量与正确性, 进而缩短设计的开发周期与成本, 探究以模型驱动及验证为主导的系统工程方法在民用飞机设计领域的适用性, 建立民用飞机设计的系统工程框架, 用以支持民用飞机的可靠设计与高效交付。以Harmony SE建模方法为切入点, 介绍其工作流程和建模思想; 分析民用飞机在系统工程实践中出现的突出问题, 说明Harmony SE方法在民用飞机系统工程领域的适用性, 建立民用飞机设计的系统工程实践体系; 以油箱增压组件为研究对象, 应用实践体系开展组件级系统工程实践。结果表明, 文中所提出的民用飞机设计系统工程体系和方法能够正确合理地分配设计需求并建立完整的系统模型, 有助于提升现阶段民用飞机设计的效率与准确性。